2008
DOI: 10.1136/sti.2008.031310
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the spread of HIV and other sexually transmitted infections among men who have sex with men infected with HIV in Lima, Peru

Abstract: Objectives-To assess the prevalence of sexually transmitted infections (STIs), frequency of sexual risk behaviors, and relationship between knowledge of HIV infection status and sexual risk behavior among HIV-infected men who have sex with men (MSM) attending an STI clinic in Peru.Methods-We recruited a convenience sample of 559 MSM from a municipal STI clinic in Lima, Peru. Participants completed a survey and provided blood for HIV, Syphilis, and HSV-2 antibody testing, and urine for gonorrhea and chlamydia n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…Syphilis also shows high prevalence among MSM, and this sexually transmitted infection (STI) is an important biological factor associated with HIV infection 1,2 . Recent studies and literature reviews point to growing prevalence of syphilis in the MSM population 5,6,7,8,9 , exceeding 30% in some countries of Latin America 2,6,7,8 and Asia 9 , confirming a previously reported trend 2 . In Brazil, a 14% lifetime history of syphilis among MSM was recently estimated by the survey Behavior, Attitudes, Prac-…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Syphilis also shows high prevalence among MSM, and this sexually transmitted infection (STI) is an important biological factor associated with HIV infection 1,2 . Recent studies and literature reviews point to growing prevalence of syphilis in the MSM population 5,6,7,8,9 , exceeding 30% in some countries of Latin America 2,6,7,8 and Asia 9 , confirming a previously reported trend 2 . In Brazil, a 14% lifetime history of syphilis among MSM was recently estimated by the survey Behavior, Attitudes, Prac-…”
Section: Introductionsupporting
confidence: 68%
“…As for syphilis, the prevalence found in Salvador is close to that reported in the international literature 2,5,7,8,9 , including RDS studies with MSM 6,30 , and shows the high prevalence of syphilis among MSM interviewed.…”
Section: Discussionsupporting
confidence: 50%
“…Our study revealed the prevalence of syphilis, as indicated by TPHA seroreactivity, was approximately 1 in 3 at baseline with 5.8 incident cases per 100 person-years of follow-up. By comparison, the 33% prevalence of syphilis among HIV-infected patients in Taiwan was considerably higher than 17.4% of HIVinfected MSM in Amsterdam [9], 4.8% in Thailand [2], or 2.9% in Los Angeles [8], but similar to 35.5% in Lima, Peru [29]. The observation that ten (10.4%) patients with new episodes of syphilis all were MSM, was consistent with other studies that have shown high incidence rates of syphilis among MSM with HIV in Los Angeles [8], Amsterdam [9], and London [10].…”
Section: Discussionmentioning
confidence: 63%
“…A recent study among HIV-infected MSM attending an STI clinic in Lima, Peru [23] showed that substance use prior to sex was common; however, substance use was not found to be significantly associated with recent unprotected anal intercourse. In Brazil, recent drug use, including marijuana, crack cocaine, amphetamines, and ecstasy, was significantly higher among MSM sex workers than among the general MSM population (56 vs. 27%, respectively) [24].…”
Section: Substance Use Among Men Who Have Sex With Men In Developing mentioning
confidence: 97%